LEGAL TECH IN LEGAL EDUCATION: GLOBAL PERSPECTIVES AND CHALLENGES FROM THE LATVIAN - UKRAINIAN EXPERIENCE - Palkova, Karina; Agapova, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The paper examines legal rules covering the legal industry and the field of legal education against the background of fast-growing innovation technology and it’s influence. The field of legal education faces with several transformation processes. Thus, educators should be ready to prepare law students for innovations in the legal field as well. The era of legal technology (or “Legal Tech”) is becoming a crucial element of modern lawyers. According to several reports, Legal Tech brings new trends for a lawyer. Such profession faces new challenges, therefore from the educational point of view it is important to prepare students for those changes. The work on national and global level in the field of policy planning documents is needed. Authors found out that nowadays legal education has a weakness that relates to insufficient cooperation with such vital elements as technology and innovation. Law science and technology cannot be considered separately taking into account changes in the global disciplines. Legal Tech in the legal education system can be implemented on several educational levels. Legal Tech education should take part on university level to instill in young lawyers a taste for progressive technologies from the student's bench.